Herbaceous plant diversity across fire created edges in continental holm oak woodlands - Azevedo, João (2010)
We analyzed herbaceous plants distribution across edges of holm oak (Quercus rotundifolia) woodlands created and maintained by fire in order to describe plant community structure across edges and to evaluate the role of fire in the patterning of plant diversity at the patch scale. We recorded abundance in twelve 60 m long sampling lines placed perpendicularly to the woodlands boundary at 1, 5, 10, and 20m outside and 0, 1, 5, 10, 20, and 40m inside the woodlands, using the line intercept method (2 x 10 m line parallel to the boundary). In the same locations, we measured tree and shrub cover, height and density and recorded time since last fire disturbance. Data was analysed graphically and statistically using multivariate ordination analysis techniques, namely CCA. Results indicated that, on average, herbaceous species richness was higher outside than inside the woodlands and peaked 1m outside the boundary. Time since last fire in adjacent shrublands affected richness patterns across edges. Richness was higher outside than inside in young adjacent shurblands, higher inside than outside in old shrublands and peaked 1m outside in intermediate age shrublands, interior, exterior and edge (1m outside the boundary) species and locations were well correlated with explanatory variables reflecting the interior exterior woodland gradient sampled and shrub recovery after fire.